Critically Compassionate Intellectualism in Teacher Education: The Contributions of Relational–Cultural Theory. (September 2019) - Rector-Aranda, Amy
Cammarota and Romero describe how they utilized a framework they call critically compassionate intellectualism (CCI)—a trilogy of critical pedagogy, authentic caring, and social justice–oriented curriculum—to lift up previously disempowered Latinx youth. CCI can also serve as an appropriate framework for emancipatory pedagogy and curriculum in teacher education and other settings, especially those committed to a mission of educational justice for our most disadvantaged students. Because the compassion element in CCI is understudied in teacher education, yet crucial to the success of the framework as a whole, in this article, I apply the tenets of relational–cultural theory (RCT) to enhance existing understandings of this component. Based on feminist theories of psychosocial and moral development, RCT expands the original framework to account for varied experiences of privilege and vulnerability when applying CCI beyond its original contexts while retaining core emphases on relationships, empathy, and associated aspects of authentic caring.